PENINGKATAN MANAGEMEN LABORATORIUM SEBAGAI UPAYA MEWUJUDKAN PRASARANA PENDIDIKAN YANG AKTIF DAN BERDAYA GUNA DI SMAN 2 BONE - Andi Trisnowali MS,; Sri Wahyuni,; Syamsuria, Syamsuria; Muhammad Yany,; Marwah, Marwah (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The laboratory is a place for monitoring, experimenting, practicing and testing the concept of knowledge and technology. Science laboratory management includes planning, organizing, regulating, recording, maintaining, and funding. The function of the science laboratory to improve the quality of student learning depends on the teacher's view of science and learning. The purpose of the activity is to provide training to teachers and laboratory assistants in high schools. The method in carrying out activities offline is the lecture method and question and answer between the presenters and activity participants. The target of this service activity is a high school biology science teacher. The results of the service are that 70% of the participants strongly agree and 30% of the participants agree that the activities regarding laboratory management are in accordance with their needs. For 65% of participants stated strongly agree and 35% of participants agreed that the delivery of material on laboratory management activities can be understood by participants. For 90% of participants stated strongly agree and 10% of participants agreed that the results of the extension activities can be implemented at school. The conclusion of this activity is that this service activity is very much needed by teachers, especially the head of the laboratory and laboratory assistant in improving their competence.